Body shaming and body image issues - Gould, Sloane (Topics today., 2022)
"Throughout the ages, the idea of a 'perfect' body has always existed, although what that kind of body is has changed. Today, many people still absorb these expectations of perfection and seek validation through social media and other platforms. This in turn has led to increasing instances of body shaming. This volume examines the complex issue of body image in today's society . . . illustrate[s] the difficulties people face in appreciating and enjoying their bodies. It also provides tips for developing a more positive body image and dealing with body shaming"--Provided by publisher.